Virtual teaching experiences for medical students during the COVID-19 pandemic: advantages and disadvantages - Mohd Faeiz, Pauzi; Siti Norazlina, Juhari; Abdul Karim, Othman; Vivekananda, Gunasekaran; Salman, Amiruddin (2020)
The best books for medical students are their patients in the bedside. However COVID-19 pandemic already changed the educational landscape from traditional methods to the virtual classroom. Movement control order (MCO) have made teaching and learning in the hospital, clinical skills laboratory and tutorial suspended. So at Faculty of Medicine, Universiti Sultan Zainal Abidin, novel virtual teaching methods such as webinars and Moodle learning management system (LMS) were used to replace traditional medical teaching during the COVID-19 pandemic. We organized webinars on relevant topics. These were viewed via Webex and included medical topics and clinical scenario discussions. Medical webinars were recorded and uploaded to Telegram group. Notes and clinical scenario discussions were uploaded in Moodle LMS, Knowledge and E-learning Integrated Platform (KeLIP) UniSZA. 32 webinars were organized by Anaesthesiology Unit with 448 attendees total. 12 webinars were uploaded to Telegram group, 12 lecture notes and 28 clinical scenario discussions were uploaded to KeLIP, a Moodle LMS. We received great feedback for all webinars and Moodle LMS. Virtual teaching is useful for teaching theory; attendees can watch anywhere, easily recorded for later viewing, no room bookings and no need for social distancing However the main disadvantage of note for airway and anaesthetics skill is inability to obtain hands-on practice. We feel virtual teaching provides continuing teaching and learning during pandemic crisis.